Crecimiento y utilización del alimento de la trucha arco iris en Costa Rica, en régimen de cultivo intensivo (ING) - Günther Nonell, Jorge (1993)
Growth and feed utilization parameters of intensive commercial rainbow trout (Oncorhynchus mykiss) culture in Río Macho, Orosi, Costa Rica, are presented (average of 5 culture periods), together with the monthly variations in dissolved oxygen, temperature and water flow in the Jucó spring passing by the station. An artificial diet with locally available ingredients was formulated and used. The performances obtained were comparable to the best results reported for industrial trout culture in temperate countries, and could be maintained all the year in Costa Rica. Regression equations are obtained for the growth and feed utilization parameters analyzed. The recommended daily feed rations are presented graphically in % of body weight for trout between 5 and 200 grams and for temperatures between 8 and 20 °C.